Proteomic profiling in Drosophila reveals potential dube3a regulation of the actin cytoskeleton and neuronal homeostasis. - Jensen, L.; Farook, M.F.; Reiter, L.T. (PLoS ONE, 2013)
The molecular defects associated with Angelman syndrome (AS) and 15q duplication autism are directly correlated to expression levels of the E3 ubiquitin ligase protein UBE3A. Here we used Drosophila melanogaster to screen for the targets of this ubiquitin ligase under conditions of both decreased (as in AS) or increased (as in dup(15)) levels of the fly Dube3a or human UBE3A proteins. Using liquid phase isoelectric focusing of proteins from whole fly head extracts we identified a total of 50 proteins that show changes in protein, and in some cases transcriptional levels, when Dube3a fluctuates. We analyzed head extracts from cytoplasmic, nuclear and membrane fractions for Dube3a regulated proteins. Our results indicate that Dube3a is involved in the regulation of cellular functions related to ATP synthesis/metabolism, actin cytoskeletal integrity, both catabolism and carbohydrate metabolism as well as nervous system development and function. Sixty-two percent of the proteins were >50% identical to homologous human proteins and 8 have previously be shown to be ubiquitinated in the fly nervous system. Eight proteins may be regulated by Dube3a at the transcript level through the transcriptional co-activation function of Dube3a. We investigated one autism-associated protein, ATP?, and found that it can be ubiquitinated in a Dube3a dependent manner. We also found that Dube3a mutants have significantly less filamentous actin than wild type larvae consistent with the identification of actin targets regulated by Dube3a. The identification of UBE3A targets is the first step in unraveling the molecular etiology of AS and duplication 15q autism.